How Eco-Anxiety Is Affected by Community Health Status and Climate Justice Determinants: An Exploratory Study in Young Population - Melissa Jimenez Gomez Tagle; Domenico Vito (Medical Sciences Forum)
The climate crisis, combined with the COVID-19 lockdown measures, exacerbated pre-existing psychological conditions among young people experiencing climate anxiety due to a lack of information and a diffuse sense of powerlessness. The current study aimed to find correlations between the health status of a community, the environmental determinants among youths, and how these affect their vision of climate change and their mental health. An exploratory survey was conducted among people aged between 18 and 33 years old from three continents, with a focus on emotional states related to natural disasters occurring in their regions. The online survey consisted of six questions. The pilot phase results showed that more females from India experienced stressful situations related to climate change, and that respondents aged between 18 and 20 years old were more informed about eco-anxiety. Given its growing frequency among young adults, further studies should be conducted to address the problem and create alternatives and coping mechanisms such as climate action.